Between a rock and a hard place: expatriate teacher narratives of expectation and exasperation - Desai, S (University of Exeter, 2019)
In this narrative study on self-initiated expatriate (SIE) faculty, I explore economic, professional, institutional and political discourses as experienced from the perspective of eight participants who have spent most of their working lives teaching in different parts of the world. Neilsen (2009) suggests that English Second Language (ESL) teachers are arguably in a position of privilege in that their services are in great demand across most regions of the world. He explains that not only can they have the opportunity of exploring the country of their choice, but they also participate in its culture and commerce. Far from this perception that ESL teachers are in a position of privilege, researchers have also described ESL teaching as a “marginalized profession” (Johnston 1999, p.255), that ESL teachers have a “volatile social status” (Troudi, 2009, p.67) and that there are “discriminatory hiring practices against NNESTS around the world” (Mahboob, 2010, p.7). My study on SIE faculty examines all these descriptions by analysing the narratives of SIE faculty; James, Janet, Soyal, Demi, Estee, Medo, Sami Ali and Jack - who have spent most of their working lives teaching in foreign locations across the world. Their personal and professional lives impacted by discourses of professionalism, discourses of education, socio-economic and socio-political discourses prevalent in nation states. Narrative research constitutes the research design for this thesis project. The stories that emerge from the data reflect my ontological perspective that subjects are produced in relation to the larger structures they inhabit. The sample selected for this study comprised exclusively expatriate language teachers who at the time of interview, had spent 15 or more years teaching ESL in countries other than their homelands. While other studies on ESL expatriate teachers show that expatriate teacher motivation is attributed to personality or psychological factors (Zafar-Khan, 2011; Chapman, Austin, Farah, Wilson and Ridge, 2014; ...